2020
DOI: 10.1590/fst.40418
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the inhibitory effect of chitosan on Penicillium expansum

Abstract: The antimicrobial effect of chitosan on Penicillium expansum, a major postharvest pathogen of pome fruit, and the possible mechanisms involved in its effect were examined in this study. Chitosan strongly inhibited spore germination and hyphal growth of P. expansum. Light microscopy and transmission electron microscopy observations revealed that chitosan also caused morphological changes in hyphae and conidia, such as abnormal branching and vacuolation. Proteomic changes in P. expansum after chitosan treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…It has been suggested that silver nanoparticles with large surface positions can easily produce Ag + by binding to the sulfhydral (-SH) practical groups of proteins and consequently denaturing proteins [50,51]. Silver nanoparticles can also cause denaturation and destruction of proton pumps by binding to fungal surface proteins, increasing the membrane permeability, or lipid bilayer proteins, which ultimately leads to the disruption of cell membranes [52,53]. Proteomic analysis in P. expansum was assayed by two-dimensional electrophoresis (2-DE) after chitosan treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that silver nanoparticles with large surface positions can easily produce Ag + by binding to the sulfhydral (-SH) practical groups of proteins and consequently denaturing proteins [50,51]. Silver nanoparticles can also cause denaturation and destruction of proton pumps by binding to fungal surface proteins, increasing the membrane permeability, or lipid bilayer proteins, which ultimately leads to the disruption of cell membranes [52,53]. Proteomic analysis in P. expansum was assayed by two-dimensional electrophoresis (2-DE) after chitosan treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been speculated that bacterial cells associated with silver nanoparticles can absorb silver ions, which can facilitate the generation of reactive oxygen species and consequently cause necrobiosis [57]. Silver nanoparticles can also cause DNA damage, and damage the ability of replication, cell walls, cell walls, mitochondria, chromatin, and ribosomes [53]. Chitosan can penetrate the fungal cell membrane and bind to its DNA, which can inhibit mRNA synthesis and thereby interfere with the accumulation of proteins and essential enzymes [58].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, only the most vital cells are taken into account in the CFU-method, as these must be able to form their own colony. The observations in the nutrient-rich environment may indicate that the polymer interferes in the metabolism of specific substrates, as studies have shown that chitosan interferes with RNA and protein synthesis [74][75][76][77]. Therefore, these substrates can no longer be used for biofilm formation or as a source of nutrients.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…However, in case of silver, it is suggested that NPs with large surface areas can quickly produce Ag + by binding to the sulfhydral (−SH) practical groups of proteins and, consequently, denaturing proteins [34]. Silver NPs can also cause denaturation and destruction of proton pumps by binding to fungal surface proteins, increasing membrane permeability, or lipid bilayer proteins, which ultimately leads to the disruption of the cell membrane [35].…”
Section: Antifungal Activities Of Nanoparticlesmentioning
confidence: 99%